Neonatal Hemodynamic Characteristics of the Recipient Twin of Twin-To-Twin Transfusion Syndrome Not Treated with Fetoscopic Laser Surgery - Edouard Chambon; Taymme Hachem; Elodie Salvador; Virginie Rigourd; Claire Bellanger; Julien Stirnemann; Elsa Kermorvant-Duchemin; Pierre Tissieres; Yves Ville; Alexandre Lapillonne (MDPI AG, 2022)
Background: This paper's intent is to describe the neonatal hemodynamic characteristics of recipient twins of monochorionic pregnancies complicated with twin-to-twin transfusion syndrome (TTTS), born without prenatal fetoscopic selective laser coagulation (FSLC). Methods: Retrospective analysis of hemodynamic characteristics was performed during the first five days of life of recipient twins from untreated TTTS. Results: Forty-two recipient twins were included and divided into three groups: no hemodynamic impairment (NoHI) (n = 15, 36%), isolated high blood pressure (HighBP) (n = 12, 28%), and cardiac failure group (CF) (n = 15, 36%). Patients of both CF and HighBP groups had high systolic blood pressure during the first 12 h of life and ventricular hypertrophy at early echocardiography. Cardiac failure occurred at a median age of 14 h (IQR = 6-24) and was followed by a drop in systolic and diastolic blood pressure. Acute kidney injury was more frequent (93% vs. 25%, p < 0.001) and severe (p <0.001) in the CF group than in the HighBP group. The mortality rate in the CF group was 40%. Factors associated with CF were twin anemia-polycythemia sequence (p = 0.012), very preterm birth (p = 0.040), and polycythemia (p = 0.002). Conclusion: One-third of recipient twins born without prenatal FSLC developed life-threatening cardiac failure during the first 24 h of life.